ITO microstructures regulation and properties based on deposition temperature - MA Kexin; CAO Lili; LUO Fei; ZHOU Haitao; WANG Yao; LUO Bingwei; XU Yi; LIU Song; SUN Kun (Cailiao gongcheng, 2024)
To improve the performance of thin film thermocouples for instantaneous temperature measurement on the surface of high temperature components of aeroengine， the indium tin oxide （ITO） thin films were prepared by DC magnetron sputtering. The microstructure of the thin film was regulated by the deposition temperature. The microstructure， surface morphology， thermoelectric properties and the bonding force of the films were characterized by X-ray diffractometer， scanning electron microscope， Seebeck tester and nanoscratch test， respectively. The results show that the deposition temperature directly determines the surface diffusion and growth capability of sputtering atoms， and carrier mobility of ITO， thereby improving their crystallinity and thermoelectric properties. The surface of the film presents a triangular grains morphology with a （400） preferred orientation at a deposition temperature of 450 ℃. Compared with the thin film sputtered at low temperature， it exhibits excellent crystallinity， with an interface bonding force of 10.89 mN. At the same time， the power factor of ITO significantly improves， with 400 μW/（m·K2） at 900 ℃ testing temperature， it shows good thermoelectric properties and high temperature stability.